Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1534/genetics.106.063677
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Selective Sweeps Using a Dynamically Adjusted Number of Linked Microsatellites

Abstract: There is currently large interest in distinguishing the signatures of genetic variation produced by demographic events from those produced by natural selection. We propose a simple multilocus statistical test to identify candidate sites of selective sweeps with high power. The test is based on the variability profile measured in an array of linked microsatellites. We also show that the analysis of flanking markers drastically reduces the number of false positives among the candidates that are identified in a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
61
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 38 publications
0
61
1
1
Order By: Relevance
“…These caveats can be avoided by screening a large number of markers spaced across an organism's whole genome to characterize the background levels of marker variability and differentiation (Schlö tterer 2003). Second, as the analysis of genome scan data involves multiple statistical tests, identification of false-positive footprints of selection may become an issue (Wiehe et al 2007). One way to alleviate this particular problem is to genotype more loci in the genomic regions near a candidate locus.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…These caveats can be avoided by screening a large number of markers spaced across an organism's whole genome to characterize the background levels of marker variability and differentiation (Schlö tterer 2003). Second, as the analysis of genome scan data involves multiple statistical tests, identification of false-positive footprints of selection may become an issue (Wiehe et al 2007). One way to alleviate this particular problem is to genotype more loci in the genomic regions near a candidate locus.…”
mentioning
confidence: 99%
“…One way to alleviate this particular problem is to genotype more loci in the genomic regions near a candidate locus. It is unlikely that a signature of selection emerging from a particular genomic region is false if it is detected in more than one marker locus (Wiehe et al 2007). However, while the analysis of markers flanking genomic regions of the candidate locus does not completely rule out demographic explanations, it is expected to result in a considerable reduction in the number of false positives (Thornton and Jensen 2007;Wiehe et al 2007).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The reasoning here is that the traces of selective sweeps may be distinguished from those of recent population bottlenecks, since only the former have a local effect, while the latter should have a chromosomewide effect. In a test tailored for multiple microsatellite loci, Wiehe et al (2007) found that this is often the case, but, for a certain (population genetically relevant) range of demographic parameters the false positive rate to detect selective sweeps is still unacceptably high. Other recently popularized methods to detect traces of selection are centered around the analysis of linkage disequilibrium (Kim and Nielsen 2004;Stephan et al 2006;McVean 2007) or the structure and frequency spectrum of haplotypes (Sabeti et al 2002(Sabeti et al , 2007.…”
mentioning
confidence: 99%